(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
This research focused on the grammatical construction on adjective clause found in Arthur Conan Doyle’s novel ‘Study in Scarlet’. The theory of this research used William O’grady (1997) and Chaer (2013) theory. The research design used was qualitative design. The researchers conducted this research in descriptive which explain the research with making table and some sentence for explain. Data were taken from study in scarlet novel. The researchers used library research to acquire data by reading and finding material from journals, books, blogs, and articles. about everything that has to do with grammatical categories, adjective clauses, or relative pronouns, which is the major purpose of this research. The sentences from the novel were taken and analyzed through the grammatical construction on adjective clause. After analyzing the data, the researchers discovered twenty-six adjective clauses from the novel with the British dialect.